2018
DOI: 10.1016/j.adro.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study to assess the potential impact of developing normal tissue complication probability models with accumulated dose

Abstract: PurposeThis study aimed to analyze the potential clinical impact of the differences between planned and accumulated doses on the development and use of normal tissue complication probability (NTCP) models.Methods and MaterialsThirty patients who were previously treated with stereotactic body radiation therapy for liver cancer and for whom the accumulated dose was computed were assessed retrospectively. The linear quadratic equivalent dose at 2 Gy per fraction and generalized equivalent uniform dose were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Published studies on NTCP for other organs at risk after radiation treatment comprise various patient numbers and provide different informative values. Other authors using a similar approach by generating comparable radiation plans with consistent radiation dosage reported similar limited numbers of patients as involved in this study [ 30 ]. Another publication, including a larger number of patients, merged patients from different studies to optimize existing NTCP parameters, but bore limitations, e.g., of slightly to noticeably varying radiation planning between the included studies and usage of vague data on doses for organs at risk [ 23 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Published studies on NTCP for other organs at risk after radiation treatment comprise various patient numbers and provide different informative values. Other authors using a similar approach by generating comparable radiation plans with consistent radiation dosage reported similar limited numbers of patients as involved in this study [ 30 ]. Another publication, including a larger number of patients, merged patients from different studies to optimize existing NTCP parameters, but bore limitations, e.g., of slightly to noticeably varying radiation planning between the included studies and usage of vague data on doses for organs at risk [ 23 ].…”
Section: Discussionmentioning
confidence: 94%
“…In modern approaches, the inaccuracy derived from depending on breath or other motion of organs including the stomach needs to be considered [ 29 ]. Studies showed a significant impact of motion on mean doses and respective NTCP for liver [ 30 , 31 ]. Similarly, in a study by McCulloch et al, NTCP differed between planned and accumulated dose for the stomach and duodenum [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of setup errors in dosimetric features has been reported (9)(10)(11)(12). Furthermore, these errors can result in overestimation or underestimation of probability according to the NTCP model (13)(14)(15). In other words, these errors might decrease the reproducibility of dosiomics as well.…”
Section: Introductionmentioning
confidence: 99%
“…17 The calculation of the final delivered dose can then be linked to an outcomes database, supporting the refinement of normal tissue complication models, tumor control probabilities, clinical trials, and protocol development. 18 Once the delivered dose is quantified for a population of patients, decision support tools can be developed empowering the clinical team with evidence-driven metrics to guide the decision to replan, Figure 1B.…”
mentioning
confidence: 99%